Bioactivity, phytochemistry studies and subacute in vivo toxicity of ethanolic leaf extract of white mulberry (Morus alba linn.) in female mice - Fauzi, Ahmad; Kifli, Nurolaini; Mohd Noor, Mohd Hezmee; Hamzah, Hazilawati; Azlan, Azrina (Elsevier Ireland, 2024)
Traditional uses of Morus alba L. leaf extracts (MLE) have been reported for treating hyperglycaemia and diabetes. Phytochemical compounds in the leaves demonstrated the ability to enhance insulin sensitivity and β-cell secretory function, suggesting their potential value in reducing blood glucose and treating diabetes. However, the phytochemical constituents and safety of the herbal medicines need to be verified in each experimental field from different growing areas. Studies on the phytochemistry and toxicity of Morus alba leaves in Southeast Asia, especially in Brunei, have never been investigated.